8th International Bielefeld Conference 2006: Academic Library and Information Services: New Paradigms for the Digital Age - Gastinger, Almuth (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
From 7-9 February 2006, Bielefeld University Library in North Rhine-Westphalia, Germany, was host to the 8th International Bielefeld Conference. The subject this year was Academic Library and Information Services: New Paradigms for the Digital Age. The conference has been taking place every two years since 1992 and has proved to be one of the most popular forums for librarians and university managers from Europe and beyond to hear about and discuss new concepts, strategies, services, and technologies for academic and research libraries. This year’s conference attracted almost 500 participants from 35 countries.